Nonbacterial thrombotic endocarditis of a bioprosthetic valve: Questions to ponder before replacement of the valve. Issue 5 (10th April 2020) - Ram, Duvuru; Armstrong, Guy; Khanijow, Vinod; Sibal, Amul Kumar
Abstract: Nonbacterial thrombotic endocarditis (NBTE) of bioprosthetic valves is extremely rare. We report a 67‐year‐old lady with early bioprosthetic "failure" that at reoperation was proven to be NBTE. The choice of a prosthesis in this condition may have implications for patients' late clinical course.